Film genre reader IV - Grant, Barry Keith, 1947- (University of Texas Press, 2012)
"Newly revised and expanded nearly a decade after the third edition, Film Genre Reader is the standard reference and classroom text for the study of genre in film, with more than 25,000 copies sold. This fourth edition adds new essays on genre definition and cycles, action movies, science fiction, and heritage films, along with a comprehensive and updated bibliography. The volume includes over thirty essays by some of film's most distinguished critics and scholars of popular cinema, including Charles Ramz Berg, John G. Cawelti, Celestino Deleyto, David Desser, Thomas Elsaesser, Steve Neale, Thomas Schatz, Paul Schrader, Vivian Sobchack, Janet Staiger, Linda Williams, and Robin Wood"--